PERSINGGUNGAN POLITIK DAN PROSTITUSI DALAM PUISI - Muhajir . (Universitas PGRI Semarang, 2014)
The purpose of this research is to find the intersection of politics andprostitution in poems entitled ?óÔé¼?ôBersatulah Pelacur-Pelacur Kota Jakarta?óÔé¼?Ø by W.S.Rendra and ?óÔé¼?ôPidato Akhir Tahun Seorang Germo?óÔé¼?Ø by F. Rahardi. How is the publicperception of prostitutes? How the authors position of prostitutes in his poetry? Thisresearch using structural theory and descriptive analytical research method. Afteranalyzing two poems, the researcher concluded that (1) Both authors use poems as amedium for criticism of the government. (2) The public perception of the prostitutes isbad, They are the bearers of state catastrophe, but the authors through his poemsdefend them because according to the authors prostitutes are victims ofmismanagement of state. (3) in the poem ?óÔé¼?ôBersatulah Pelacur-Pelacur Kota Jakarta?óÔé¼?Ø byRendra occur politicization where prostitution is sold as issue of politics. Whereas in thepoem by f Rahardi not found. The use of poetic language rendra more assertive andprovocative and against the injustice committed by politicians and officials . The use ofpoetic language F. Rahardi more relaxed, joking, and appeal to submit problems to God(5) The use of poetic language F Rahardi softer because he did not want to suffer likeW.S. Rendra were eliminated by the new order government.Keywords: prostitution, politics, poetry